THE ROLE OF ACTOR-NETWORK-THEORY IN SELF-HELP HOUSING: A CASE STUDY OF THE AUTHOR'S HOUSE - Putra Bagus Khalis (Jurnal Arsitektur ZONASI, 2022)
This paper aims to understand the process of self-help housing through the Actor-Network-Theory approach using the author's house as a case study. The underlying theory in this paper is the Actor-Network-Theory proposed by Latour (2005), how actors and networks in social and self-help housing proposed by Turner (1976), how residents build their own houses. This paper uses a narrative approach, how the author and the owner of the house are directly involved and tell their involvement in a case study to explore the role of Actor-Network-Theory in the author's self-help housing. The finding of this study is that in the author's self-help housing there is an important role between actors so as to create a network that is strengthened by the presence of objects. Three such actors, homeowners, architects, and construction workers form a network called the trinity in architecture, namely the client, the architect and the craftsman (Fathy, 1973).  A social network can be formed if there are actors who act or act with each other with other actors. The actions or actions of the first actor will affect the actions of subsequent actors. Making decisions at each stage of the self-help process depends on discussion between actors. The exchange of ideas is what makes this process a lesson for future actors.